Overview about HCMGIS System and Topology of GIS Data for some HCM Problems - Vũ Thanh Nguyên (Journal of Technical Education Science, 2007)
Ho Chi Minh city is deploying the project “Ho Chi Minh City Geographic Information System - HCMGIS” with an objective to support the reform in administration and urban management. This project is a general project for urban management in Ho Chi Minh city by using GIS technology. The standard data of the city map were built basically but usually not in topology standard. Author and his colleagues reseached some algorithms and solutions to convert the GIS notopo data to GIS topo data, built topo conversion tools and used that data to build many other applications to serve HCM GIS problems such as plan, traffic, electric power, post, etc.